Do general practitioners follow treatment recommendations from guidelines in their decisions on heart failure management? A cross-sectional study. Issue 9 (16th September 2013) - Swennen, Maartje H J; Rutten, Frans H; Kalkman, Cor J; van der Graaf, Yolanda; Sachs, Alfred P E; van der Heijden, Geert J M G
Abstract : Objective: To investigate whether general practitioners (GPs) follow treatment recommendations from clinical practice guidelines in their decisions on the management of heart failure patients, and assess whether doctors' characteristics are related to their decisions. Design: Cross-sectional vignette study. Setting: Continuing Medical Education meeting. Participants: 451 Dutch GPs. Main outcome measures: Answers to four multiple-choice treatment decisions in clinical vignettes of a patient with heart failure and a reduced ejection fraction. With univariable and multivariable regression analyses, respondent characteristics were related to optimal treatment decisions. Results: Of the 451 GPs, none took four optimal decisions: 7% considered stopping statin treatment, 36% initiated β-blocker treatment at a low-dose and 4% doubled the β-blocker in the up-titration phase. Finally, for our vignette patient now also suffering from chronic obstructive pulmonary disease, 45% of the GPs continued β-blocker therapy even when they considered prescribing a long-acting β2-agonist. While the relation between respondent characteristics and each decision was very different, none was independently associated with all four decisions. Giving priority to evidence-based medicine was independently related to stopping statin treatment and doubling the β-blocker in the up-titration phase. Conclusions: GPs seem not to follow treatment recommendations from clinical practice guidelines in their decisions on the management of heart failure patients. The recommendations from guidelines may appear counterintuitive when statin treatment needs to be stopped when a patient feels comfortable, or when a β-blocker should be up-titrated in patients who experience more symptoms. Giving priority to evidence-based medicine is possibly positively related to difficult treatment decisions.